Body morphology characteristics of male sprint athletes in China - Bao, C. Y.; Meng, Q. H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The 100-meter race, because of the short duration, strong competition and uncertain results is one of the most exciting and attractive events in track and field competition. However, in recent years, the performance of Chinese 100-meter male athletes has been lacking and has resulted in limited success at the Asian Games and on the world stage. In order to reduce the gap, the key is to discover and train the talent. Therefore, the focus of this research is 16-17 year old elite 100m sprinters. The study examined body morphology characteristics, and searched for the current problems and shortage of athletes. The research will be important and realistic for clarifying the training ideals, improving the training methods and strengthening the scientific literature.